KONDISI KIMIA TANAH DI BAWAH TEGAKAN PINUS (Pinus merkusii Jungh. et de Vriese) DAN PADANG RUMPUT DESA WATUTAU KECAMATAN LORE PEORE KABUPATEN POSO SULAWESI TENGAH - Tongka, Gretty Natalia Tongka Natalia; Wardah, Wardah; Yusran, Yusran (ForestSains, 2019)
The area of pine stands 25 year old are 500 ha grow at advacent of grassland. The pine stands and grassland have different effect on chemical properties of soil. The objective of tree study are to determine the soil chemical propertie of pine stand and grassland. The research was conducted from November 2017 to January 2018, located at pine and grassland area of Watutau Village, Lore Peore Sub-district, Poso District, Central Sulawesi. Analysis of chemical properties of soil samples including pH, C-organic, N-total, P-available, K-total and CEC was conducted at the Soil Science Laboratory, Faculty of Agriculture, Tadulako University. The results showed that pine stands had soil chemical conditions at a depth of 0-30 cm lower in (C-organic, P-available, K-total, and CEC) but higher in pH and N-total than on grassland areas. The soil chemical conditions in pine stands consist of pH 4.90 acid, C-organic 0.55% very low, N-total 0.09% very low, P-available 5.26 mg / 100g very low, K-total 11 , 81 mg / 100g low, CEC 4.29 cmol (+) kg-1 is very low. While soil chemical conditions on grassland area consist of pH 4.79 acid, C-organic 1.61% low, N-total 0.08% very low, P-available 9.24 mg / 100g very low, K-total 19.45 mg / 100g average, CEC 4.76 cmol (+) kg-1 is very low.